2021
DOI: 10.1192/bjb.2021.110
|View full text |Cite
|
Sign up to set email alerts
|

The mass release of migrants from UK immigration detention during the COVID-19 pandemic: what can be learned?

Abstract: Summary Convincing international evidence demonstrates that immigration detention adversely affects mental health. During the COVID-19 outbreak, additional concerns were raised about the safety and appropriateness of immigration detention. Consequently, several hundred migrants were released en masse from UK immigration detention centres, and few new detentions took place. Over 70% fewer migrants were held in detention centres in June 2020 compared with December 2019. This large ‘natural experiment’ has dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Additionally, during the early stages of the covid-19 pandemic, several hundred migrants were released from UK detention centres and almost no new detentions took place. No adverse consequences regarding immigration control were reported, demonstrating the feasibility of detaining fewer people 6. Furthermore, community alternatives in Bulgaria, Cyprus, and Poland have proved highly cost effective 7…”
mentioning
confidence: 92%
“…Additionally, during the early stages of the covid-19 pandemic, several hundred migrants were released from UK detention centres and almost no new detentions took place. No adverse consequences regarding immigration control were reported, demonstrating the feasibility of detaining fewer people 6. Furthermore, community alternatives in Bulgaria, Cyprus, and Poland have proved highly cost effective 7…”
mentioning
confidence: 92%
“…The pandemic, while tragic, has shown that warehousing human beings may be less of a necessity than previously considered. As jails and prisons across the western world have released "lower priority" incarcerated persons from custody, so have immigration detention centers (Waterman et al, 2021). In February of 2021, the average daily detention population reached its lowest since 1997 (Kassie, 2019), with 13,258 noncitizens held in Immigration and Customs Enforcement (ICE) facilities (TRAC, 2021b), or about onequarter of the 2019 average daily detention population (ICE, 2020).…”
mentioning
confidence: 99%